Complications of transanal endoscopic resection in cancer recti - R. P. Nikitenko; K. O. Vorotyntseva; S. P. Degtyarenko; O. M. Stepanovichus (Клінічна хірургія)
Objective. To study іntra- and postoperative complications in transanal endoscopic resection in patients, suffering cancer recti and to reduce this quantity.